PUDARNYA PESONA HUKUM ISLAM DI PTAI - Yusdani Yusdani; Junanah Junanah; Muhammad Husnul (Millah: Journal of Religious Studies, 2014)
The following article denotes the result of research. It tries to explain the curriculum and competencies of graduation that have been produced by Islamic law program in three Islamic universities of Yogyakarta , the State Islamic Universitas Sunan Kalijaga (UIN SUKA), Universitas Islam Indonesia (UII) and Universitas Tjokroaminoto (UCY). The research has been conducted by tracing documents and interviews with stakeholders in the three- universities. The results of this study has revealed that there are dynamics of the learning curriculum of Islamic law in three universities of Yogyakarta. The Competence of graduation from the curriculum of Islamic law is the result of the application of three universities of Yogyakarta can be categorized into two basic competencies both academic competence and professional competence. The basic of epistemological bases of Islamic jurisprudence in three universities of Yogyakarta still yet to be established form. Therefore, in order to produce the graduation, it takes the courage of stakeholders in three universities of Yogyakarta above mentioned to choose the alternative development of the study of Islamic law in the future.